Influence of Ankle Braces on the Maximum Strength of Plantar and Toe Flexor Muscles - Yamauchi, J.; Koyama, K. (International Journal of Sports Medicine, 2015)
This study sought to investigate the influence of ankle braces on maximum strength of plantar and toe flexor muscles. 21 healthy participants volunteered, and their maximum isometric toe flexor muscle strength (TFS), plantar flexor muscle strength (PFS) and passive range of motion of the ankle joint (ROM) were measured. TFS, PFS and ROM were compared among barefoot as a control (BAR), ankle support (SUP) and ankle splint (SPL) conditions. TFS was significantly lower in SPL (90.7±32.5 N, p<0.0001) compared to BAR (117.3±39.5 N) and it was significantly lower in SPL than in SUP (110.5±36.7 N, p=0.0001), whereas it was not significantly different between SUP and BAR (p=0.2587). On the contrary, PFS and ROM were significantly lower in SUP (p=0.0087 for PFS; p=0.0095 for ROM) and SPL (p<0.0001 for PFS; p<0.0001 for ROM) compared to BAR, and they were significantly lower in SPL than in SUP (p=0.0073 for PFS; p<0.0001 for ROM). The ankle support could provide ankle joint stabilization without a large decrease in the muscle strength of the foot. The proper use of an ankle brace is required to prevent major impairment of the muscle functions of the ankle-foot complex.
Keywords: ankle stabilizers; toe grip dynamometer; isometric muscle contraction